Sophie Claiborne's Upset Stomach - an Ornithine Transcarbamoylase Deficiency Problem-Based Learning Case - Marshall Anderson; Mary Kirkish (Association of American Medical Colleges, 2007)
Abstract This resource is a problem-based learning (PBL) case featuring a female patient who has problems with food containing protein. As the case progresses it becomes evident that there is a problem handling any quantity of protein and that this problem may be due to a defect in the urea cycle. A liver biopsy confirms that the patient has 52% of the normal ornithine transcarbamoylase (OTCase) activity. At age 18, Sophie is selected as a participant in a gene therapy trial at the University of Pennsylvania to introduce a good copy of the OTCase gene into the liver; however, the trial is stopped before Sophie receives the therapy because of the death of a previous candidate. This case illustrates how even a partial deficiency in a crucial enzyme in a metabolic pathway can have dramatic effects. Students learn how to manage metabolic defect patients and also learn the problems facing medical researchers trying to find the correct vector to insert good copies of a gene into a tissue. The case is suitable for either first or second-year medical students in either a PBL or traditional curriculum; or for third-year students in a pediatric clerkship. It could also be adapted to a team-based learning exercise.